Plant-microbes interactions in enhanced fertilizer-use efficiency - Adesemoye, Anthony O; Kloepper, Joseph W (Applied microbiology and biotechnology, 2009)
The continued use of chemical fertilizers and manures for enhanced soil fertility and crop productivity often results in unexpected harmful environmental effects, including leaching of nitrate into ground water, surface run-off of phosphorus and nitrogen run-off, and eutrophication of aquatic ecosystems. Integrated nutrient management systems are needed to maintain agricultural productivity and protect the environment. Microbial inoculants are promising components of such management systems. This review is a critical summary of the efforts in using microbial inoculants, including plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi for increasing the use efficiency of fertilizers. Studies with microbial inoculants and nutrients have demonstrated that some inoculants can improve plant uptake of nutrients and thereby increase the use efficiency of applied chemical fertilizers and manures. These proofs of concept studies will serve as the basis for vigorous future research into integrated nutrient management in agriculture.